The DREAM BIG project as a model for harmonizing early measures of parental care and parent-child interactions across epidemiological cohorts - Szekely, Eszter; Laplante, David P.; Tiemeier, Henning; Evans, Jonathan; Pearson, Rebecca M.; Bekkhus, Mona; Bakermans-Kranenburg, Marian; van IJzendoorn, Marinus H.; Wazana, Ashley (Frontiers in Child and Adolescent Psychiatry, 2023)
Parenting is a key contributor to child development. The effects of parenting, however, also depend on child characteristics, including genetic factors. A more complete appraisal of the role of parenting thus requires a comprehensive developmental model which explores questions about parenting behavior, child susceptibility to parenting, and child psychopathology. Moving forward, we need to not only be concerned about sample sizes that limit testing of comprehensive models but also the need to replicate findings across multiple settings and samples. A consortium which harmonises key measures offers the opportunity to examine these questions. The Developmental Research in Environmental Adversity, Mental health, BIological susceptibility and Gender (DREAM BIG) consortium includes six international longitudinal prospective birth cohorts to explore the early life origins of major psychiatric disorders in childhood. Here, we will provide a brief overview of parental care research, methodological limitations, and two exciting recent attempts (i.e., the DREAM BIG consortium and the CATS-project), that address key methodological challenges.